2010
DOI: 10.1128/iai.00533-10
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Antigen Peptide Vaccines againstPlasmodium falciparumMalaria

Abstract: The multiple antigen peptide (MAP) approach is an effective method to chemically synthesize and deliver multiple T-cell and B-cell epitopes as the constituents of a single immunogen. Here we report on the design, chemical synthesis, and immunogenicity of three Plasmodium falciparum MAP vaccines that incorporated antigenic epitopes from the sporozoite, liver, and blood stages of the life cycle. Antibody and cellular responses were determined in three inbred (C57BL/6, BALB/c, and A/J) strains, one congenic (HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 63 publications
1
32
1
1
Order By: Relevance
“…This results in a large macromolecule with a unique 3-dimensional configuration that has a high molar ratio of peptide antigen to core molecule and does not require a carrier protein for elicitation of the immune response. The MAP system can deliver not only multiple B-cell but also Tcell epitopes and has already been shown to be valuable in vaccine development for infectious diseases and tumors (18)(19)(20)30).…”
Section: Discussionmentioning
confidence: 99%
“…This results in a large macromolecule with a unique 3-dimensional configuration that has a high molar ratio of peptide antigen to core molecule and does not require a carrier protein for elicitation of the immune response. The MAP system can deliver not only multiple B-cell but also Tcell epitopes and has already been shown to be valuable in vaccine development for infectious diseases and tumors (18)(19)(20)30).…”
Section: Discussionmentioning
confidence: 99%
“…53 Reverse and forward vaccinology approaches for vaccine development have also recently confirmed that combining multiple antigens in a vaccine provides broader protection against different strains of a pathogen than individual antigens. [54][55][56] Simultaneously, by eliminating extraneous sequences or antigens that may be detrimental to the induction of protective immunity, such vaccines may potentially be more immunogenic and protective than whole-organism vaccines. 57,58 The current state-ofthe-art peptide vaccine is a complete synthetic inflammatory product that is ingested by professional antigen-presenting cells and stimulates both CD4+ and CD8+ T-cells.…”
Section: Resultsmentioning
confidence: 99%
“…They have several advantages as immunogens, including simple antigenic composition, low cost, ease of manufacture, control of production scale, absence of risk of reversion to the wild-type, virulent form, and better stability compared with other vaccine technologies. Presentation of synthetic peptides as MAPs has been shown to be valuable in vaccine development [3,7,18,19]; since the increased molecular weight and repeating peptide structure of MAPs have been shown to improve immunogenicity [20].…”
Section: Discussionmentioning
confidence: 99%